COMPLEX CHARACTERISTICS OF GEOLOGICAL/GEOTOURISTIC OBJECTS OF THE SKOLE BESKYDS AS INDICATORS OF TECTONIC-SEDIMENTARY PROCESSES IN THE OUTER CARPATHIANS - Hnylko, О.; Bogdanova, М.; Bozhuk, Т. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A description of the geological/geotouristic "weekend" excursion from Lviv to the nearest part of the Carpathians is presented with an overview of the exposed deposits of the Western European platform and the Skole Beskyds on the route Lviv - Mykolaiv - Verkhnye Synyovydne - Kamyanka - Lviv. A comprehensive outline of the geological position of the route area is given. The main geological objects and observation points (stops) along the route are described. The proposed route will allow you to get acquainted with the whole complex of the sediments on both the Tethys Paleocean margin and the ancient Paratethys Sea, to trace some indicators of the beginning of growth of the Carpathian Mountains, as well as to see the main oil-generating strata of the entire Carpathian arc. In observation points 1 and 2 near Mykolayiv, we observe Miocene shallow-water sandy formations of Paratethys. Point 3 is the Uhersk gas field located in the Carpathian Foredeep. In point 4 (Verkhnye Synyovydne) the lithofacies of the transition link between the Tethys and Paratetys deposits are exposed, and the Paratetys deposits here are expressed by the Menilite Formation (Oligocene) - the main oil-generating stratum of the Carpathians. In points 5 and 6 (Kamyanka Stream) we observe the deepest-water sedimentary formations of the Outer Carpathian segment of the Tethys – the products of catastrophic (including turbidite) currents and background (hemi)pelagic sedimentation.
Keywords: Ukrainian Outer Carpathians; Skole Beskyds; turbidites; geological excursion; geotourism